The Impact of Climate Change on Agricultural Productivity and Economic Stability in Rural Zimbabwe - Mugambiwa, Shingirai Stanley; Rapholo, Frank Selelo (CV. Literasi Indonesia, 2024)
This study examines the relationship between climate change, agriculture, and the economic trajectory of rural Zimbabwe focusing on Mutoko district, a region that largely depends on subsistence agriculture. Over the years, the region has experienced a drastic reduction in agricultural production owing to the variability in rainfalls, long draughts, as well as extreme weather conditions. These climatic variations have resulted in lower output in agricultural activities, economic crisis, and increasing instances of hunger and poor nutrition amongst households and the economy. A qualitative exploratory research design was adopted, and data was collected through semi-structured interviews, focus group discussions, and participant observation from 30 smallholder farmers in the Mutoko district. The study found that climate change has significantly affected farming practices resulting in decreased crop production. This has strained the economic welfare of the region and increased the rate of food insecurity. The paper concludes by recommending a need for improved climate policy, encouraging the adoption of climate-resilient farming practices, and appropriate assistance to marginalized communities as a means towards improving the community’s resilience to climate change and sustainable livelihoods in rural Zimbabwe.